The relevance and implications of signet-ring cell adenocarcinoma of the oesophagus. Issue 3 (6th December 2017) - Bleaney, Christopher William; Barrow, Mickhaiel; Hayes, Stephen; Ang, Yeng
Abstract : Aim: To review the current understanding of signet-ring type oesophageal adenocarcinoma including evidence for prognosis. Methods: We conducted a literature search of nine healthcare literature databases for articles detailing the biology and clinical outcomes of signet-ring cell adenocarcinoma of the oesophagus. The impact of signet-ring cell morphology was analysed and detailed in written text and tabular format. Current understanding of the biology of signet-ring cell adenocarcinoma of the oesophagus was summarised. Results: Signet-ring cell carcinoma was represented in 7.61% of the 18 989 cases of oesophageal carcinoma reviewed in multiple studies. The presence of signet-ring cells conferred a worse prognosis and these tumours responded differently to conventional treatments as compared with typical adenocarcinoma. Little is known about the biological features of signet-ring cell adenocarcinoma of the oesophagus. Work in gastric lesions has identified potential targets for future treatments such as CDH1 and RHOA genes. Categorisation of signet-ring cell carcinomas by the proportion of signet-ring cells within tumours differs among clinicians despite WHO criteria for classification. The current UK guidelines for histopathological reporting of oesophageal tumours do not emphasise the importance of identifying signet-ring cells. Conclusion: The presence of signet-ring cells in oesophageal adenocarcinomas leads to poorer clinical outcomes. Current understanding of signet-ring cell biology in oesophageal cancer is limited.